2016
DOI: 10.1111/and.12535
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation levels of imprinted and nonimprinted genes DMRs associated with defective human spermatozoa

Abstract: Asthenozoospermia (AS) is a common cause of human male infertility. Recent studies have shown significant associations of aberrant DNA methylation in spermatozoa with male infertility. The aims of the this investigation were to assess the changes in DNA methylation of known imprinted genes (MEST, GNAS and H19), novel imprinted gene (FAM50B) and nonimprinted genes (LINE-1 and P16) DMRs in the spermatozoa of infertile men with single-factor AS. Semen samples were obtained from 46 AS patients and 49 age-matched n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…In conclusion, DNA methylation has been closely associated with male infertility (66,121). Understanding the mechanisms underlying DNA methylation is particularly important in order to develop therapeutic strategies for male genital system diseases caused by abnormal sperm DNA methylation.…”
Section: Resultsmentioning
confidence: 97%
“…In conclusion, DNA methylation has been closely associated with male infertility (66,121). Understanding the mechanisms underlying DNA methylation is particularly important in order to develop therapeutic strategies for male genital system diseases caused by abnormal sperm DNA methylation.…”
Section: Resultsmentioning
confidence: 97%
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent meta‐analysis (Santi, Vincentis, Magnani, & Spaggiari, ) including 24 studies also showed that male infertility is associated with abnormal sperm DNA methylation of H19, MEST and SNRPN genes. Other studies reported that DNA methylation levels of imprinted genes IGF2, PEG3, ZAC, LIT1, SNRPN and non‐imprinted repetitive elements, such as LINEs and ALU , were altered in abnormal spermatozoa (Boissonnas et al, ; El Hajj et al, ; Kobayashi et al, ; Urdinguio et al, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific epigenetic alterations of the IGF2‐H19 locus were detected in patients with teratozoospermia and oligo‐astheno‐teratozoospermia (Boissonnas et al, ). Xu et al () reported abnormal methylation levels of P16, MEST, GNAS, FAM50B and LINE‐1 DMRs in patients with asthenozoospermia. For idiopathic non‐obstructive azoospermia (NOA) patients, the evaluation of epigenetic alteration relied on testicular tissue because they have no spermatozoa in their semen (Wu, Ding, Tan, Li, & Xiong, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation